ANTIOXIDANT ACTIVITY TEST OF A FUNCTIONAL DRINK MIXED FROM MORINGA LEAVES DECOCTION EXTRACT (Moringa oleifera) AND GARLIC DECOCTION EXTRACT (Allium sativum) USING THE DPPH METHOD - Rusita, Youstiana Dwi; Hastuti, Rini Tri (Jurnal Jamu Kusuma, 2024)
Antioxidants are essential to increase endurance and maintain the immune system to prevent the entry of various diseases. Antioxidants are found in many fruits and vegetables, one of which is moringa and garlic. Moringa leaves and garlic have properties as a source of antioxidants and can increase the body's immune system so that it can be processed into functional drinks. The manufacture of functional drinks MOSA (Moringa oleifera (Leaves) & Allium sativum (Garlic)) uses the flavor of palm sugar, which is known to have antioxidant activity. The purpose of this study was to determine the pH and antioxidant activity of functional beverages MOSA. In this study, pH testing used a pH meter, and antioxidant activity testing used a UV-Vis spectrophotometer with the DPPH method. The maximum wavelength of the control solution obtained is 518 nm, with an absorbance of 0.786. The results showed that the average pH was 6.574, and the IC50 was 45.931. The low pH in MOSA functional drinks is low acidic and has very strong antioxidant activity. The low pH value of MOSA functional beverage meets the quality requirements after MOSA is dissolved with water so that it has the potential to be a functional drink.